Elaboration Likelihood Model (ELM) As Interpersonal Communication in Persuading Consumers in the Era of Disruption - KAROLINE, Rince; SUNARTO, Sunarto; JAMALULLAI, Jamalullail; ARIANI, Nafiah (PT Keberlanjutan Strategis Indonesia, 2023)
The disruption era is a phase of the marketing concept that combines online and offline interactions between companies and consumers; both have their respective roles and complement each other. PT Honda Maju Mobilindo uses offline and online methods to sell its products. Personal selling is one of PT Honda Maju Mobilindo's most dominant offline methods to support promotional activities. Honda vehicles are included in the high-involvement product category, so human-to-human contact is needed to deliver messages to potential customers. This study uses the Elaboration likelihood model (ELM) with route central and peripheral route dimensions to analyze research problems. This research uses a mixed method with a postpositivism paradigm, a type of case study research, and data collection techniques using observation, interviews, documentation, and questionnaires. Data analysis techniques use the Miles & Huberman model. The results showed: that Honda consumers took the central route when processing received messages. The novelty in this research is the Elaboration model of the central route of automotive products in the era of disruption, which is the suitable communication model for promoting automotive products by combining online and offline interactions. In the era of technology, properly implementing promotional activities is not enough to be done online. However, offline methods are needed to ensure that consumers receive satisfactory service for purchased products.